Manajemen Pendidikan Agama Islam dalam Membangun Moderasi Beragama di Sekolah - Yuyun Alfasius Tobondo (Asosiasi Riset Pendidikan Agama dan Filsafat Indonesia, 2025)
This study aims to analyze the role of Islamic education management in fostering religious moderation in schools. Amid the challenges of globalization and technological advancement, Islamic education faces the need to reflect values of moderation, tolerance, and inclusivity. The research method employed is a literature study with a qualitative narrative approach, evaluating previous studies related to this topic. The findings indicate that effective Islamic education management can be a strategic instrument in instilling moderation values through curriculum, policies, and learning practices. However, the implementation of religious moderation still faces obstacles, such as the lack of systematic managerial strategies and institutional challenges. This study recommends the development of a more specific and structured Islamic education management model to support religious moderation in schools. Thus, it is expected to create an inclusive and harmonious educational environment capable of shaping students' moderate and tolerant character.